Dziecko w twórczości księdza Jana Twardowskiego - Stępińska, Katarzyna (Starość i młodość w literaturze i kulturze, 2016)
Father Jan Twardowski is a religious poet. His poetry is a masterpiece of wonder at the beauty of theworld and its creatures. Children have a special place in his work. Not only he wrote about children, butalso he wrote for them. The child in his poetry is someone who is constantly surprised, who is askinga lot of questions, who wants to explore the world and admire him, because everything he sees is somethingnew and full of mystery. His poetry is also very widely read by adults because they can discovera child in themselves and they may again and more fully explore the world.